MINING POLICY CONFLICT: Recruitment of Local Workers in Morosi Industrial Estate, Konawe Regency, Southeast Sulawesi - La Ode Muhammad Elwan; Muhammad Yusuf; La Ode Herman Halika (Halu Oleo University, 2022)
This study aims to determine the MINING POLICY CONFLICT: Recruitment of Local Workers in Morosi Industrial Estate, Konawe Regency, Southeast Sulawesi. The focus of the study is to find the design of mining policies and the impact of mining as well as the adoption model for the application of mining policies in the recruitment of local workers in the Morosi Industrial Estate. This type of research is qualitative with an analytical descriptive design, used to collect data by researchers and present descriptive data with in-depth analysis. This research was conducted in the administrative area of the Morosi Industrial Estate which is within the territory of the Konawe Regency Government of Southeast Sulawesi Province. The results of the study explain that the Konawe Regency Government is able to take advantage of opportunities to increase regional economic growth even during the Covid-19 pandemic by opening up investment opportunities and massive employment through collaboration with PT. VDNI and PT. OSS. The dynamics of mining conflicts in the recruitment of local workers can be minimized so that the Konawe Regency Government and the Konawe people feel that it is a reduction in unemployment and poverty. Furthermore, currently, the adaptation that can be done by the Konawe Regency Government is to increase the competence of the local community of prospective workers according to the needs of mining companies